Chronic ulcerating genital herpes simplex virus infection: A diagnosis mislead by HIV infection - Sudip Parajuli; Yogesh Acharya; Sandhya Bagariya Rathi; Upama Paudel (Our Dermatology Online, 2014)
We report a case of chronic herpes simplex in a 27 year old lady presenting with a history of persistent verrucous ulcer in the natal cleft of nine months duration. The patient was diagnosed and treated initially as a case of Tuberculosis Verrucosa Cutis (TVC) based on the chronicity of the ulcer, negative HIV serological tests and histopathological findings. The diagnosis had to be revised as the lesion was increasing in size and the patient was not responding to treatment even after completing antituberculous treatment for six months. Repeat histopathological examination and immunohistochemistry showed DNA of herpes simplex. Based on this finding a repeat HIV serology was sent which was positive. The ulcer healed after a course of acyclovir. The case is being reported to highlight the importance of considering chronic herpes simplex infection in a case of chronic genital ulcer. In addition this case reminds us the nature of HIV infection to mislead the diagnosis by altering the natural course of the disease process.